Rational selection of culture medium for clavulanic acid production by Streptomyces clavuligerus based on a metabolic modeling approach - Gómez-Riosa, David; Ramírez-Malule, Howard; Ochoa, Silvia; Ríos-Estepa, Rigoberto (Agriculture and Natural Resources, 2022)
Importance of the work: Clavulanic acid (CA) is a β-lactam antibiotic produced by Streptomyces clavuligerus and is an inhibitor of β-lactamase enzymes responsible for antibiotics resistance in several pathogenic bacteria. CA productivity in wild-type S.clavuligerus is low and determination of favorable environmental condition forCA biosynthesis is required. Objectives: To determine the culture conditions that promote secondary metabolismactivity in S. clavuligerus and redirection of metabolic fluxes. Materials & Methods: An in silico approach was implemented to select amino acidssupplementation to culture media as a rational strategy to promote CA biosynthesisduring cultivation. Submerged cultures of S. clavuligerus were investigated in syntheticand complex media selected according to the in silico study. Results: Amino acids supplementation favored CA production over the complex media.Fed-batch operation favored both biomass maintenance and CA accumulation comparedwith the batch operation. The increase in the agitation velocity had a positive effect onbiomass and CA accumulations. Main finding: The defined media lead to specific nutrients starvation that act as stressfactors potentially triggering the CA secretion. The in silico analysis showed that duringphosphate-limited conditions, the high concentration of glutamate boosts the urea cyclefrom aspartate, increasing the carbon flux toward arginine and CA.